HIV-1 drug resistance in people on dolutegravir-based antiretroviral therapy: a collaborative cohort analysis - Loosli, Tom; Hossmann, Stefanie; Ingle, Suzanne M; Okhai, Hajra; Kusejko, Katharina; Mouton, Johannes; Bellecave, Pantxika; van Sighem, Ard; Stecher, Melanie; d'Arminio Monforte, Antonella; Gill, M John; Sabin, Caroline A; et al. (The lancet HIV, 2023)
The widespread use of the integrase strand transfer inhibitor (INSTI) dolutegravir in first-line and second-line antiretroviral therapy (ART) might facilitate emerging resistance. The DTG RESIST study combined data from HIV cohorts to examine patterns of drug resistance mutations (DRMs) and identify risk factors for dolutegravir resistance. We included cohorts with INSTI resistance data from two collaborations (ART Cohort Collaboration, International epidemiology Databases to Evaluate AIDS in Southern Africa), and the UK Collaborative HIV Cohort. Eight cohorts from Canada, France, Germany, Italy, the Netherlands, Switzerland, South Africa, and the UK contributed data on individuals who were viraemic on dolutegravir-based ART and underwent genotypic resistance testing. Individuals with unknown dolutegravir initiation date were excluded. Resistance levels were categorised using the Stanford algorithm. We identified risk factors for resistance using mixed-effects ordinal logistic regression models. We included 599 people with genotypic resistance testing on dolutegravir-based ART between May 22, 2013, and Dec 20, 2021. Most had HIV-1 subtype B (n=351, 59%), a third had been exposed to first-generation INSTIs (n=193, 32%), 70 (12%) were on dolutegravir dual therapy, and 18 (3%) were on dolutegravir monotherapy. INSTI DRMs were detected in 86 (14%) individuals; 20 (3%) had more than one mutation. Most (n=563, 94%) were susceptible to dolutegravir, seven (1%) had potential low, six (1%) low, 17 (3%) intermediate, and six (1%) high-level dolutegravir resistance. The risk of dolutegravir resistance was higher on dolutegravir monotherapy (adjusted odds ratio [aOR] 34·1, 95% CI 9·93-117) and dolutegravir plus lamivudine dual therapy (aOR 9·21, 2·20-38·6) compared with combination ART, and in the presence of potential low or low (aOR 5·23, 1·32-20·7) or intermediate or high-level (aOR 13·4, 4·55-39·7) nucleoside reverse transcriptase inhibitor (NRTI) resistance. Among people with viraemia on dolutegravir-based ART, INSTI DRMs and dolutegravir resistance were rare. NRTI resistance substantially increased the risk of dolutegravir resistance, which is of concern, notably in resource-limited settings. Monitoring is important to prevent resistance at the individual and population level and ensure the long-term sustainability of ART. US National Institutes of Health, Swiss National Science Foundation.